MODEL PENTAHELIX PADA WISATA BERBASIS MASYARAKAT DI PULAU LEMUKUTAN BENGKAYANG - Hasanah, Uswatun; Ibrahim, Ibrahim; Luqman, Luqman (I-Economics, 2023)
Beach tourism in Lemukutan Island is located in Bengkayang Regency, West Kalimantan Province is one of the tourist objects in West Kalimantan that used the concept of community-based tourism (CBT), this research uses a descriptive qualitative approach that is field research, the data in this research is collected through interview, observation and documentation. This study aims to explain the role of the community in managing tourism on Lemukutan Island and to understand the pentahelix collaboration model on tourism that synergizes other stakeholders to build tourism sustainability in after the Covid-19 pandemic, and explain the economic impact for the community of tourism on Lemukutan Island. The results showed that the community have an essential role in the sustainability of tourism, the community's ability to manage tourism can attract some other stakeholders to synergizes in developing a Lemukutan Island tourism, especially after the Covid-19 pandemic, as a result the economy of the Lemukutan Island community has also increased. The pentahelix model in tourism development on Lemukutan Island involves five main actors, namely the community or society as the main actor managing tourism, government, Business or private companies, academic and media. The participation of these stakeholders, Lemukutan Island tourism will continue to exist in the future.